The clinical complication scale of Fondazione Don Gnocchi for classifying clinical complications in patients with severe acquired brain injury: development and multicenter validation - Estraneo, Anna; Fiorentino, Maria Rosaria; Cibellis, Tommaso; Campana, Biagio; Balbi, Pietro; Carli, Valentina; Vatteroni, Elena; Devalle, Guya; Mantelli, Francesco; Villa, Mattia; Bianchi, Alessandra; Costa, Maria Concetta; et al. (Frontiers in Neurology, 2025)
IntroductionPatients with severe acquired brain injury have a high risk of developing clinical complications that affect clinical outcome and rehabilitation program. Early identification of clinical complications would allow to treat them appropriately and to prevent their worsening. However, available clinical scales for recording clinical complications are not appropriately tailored for this population. The present multicenter study aimed at developing and validating a new scale to categorize the clinical complications: the Clinical Complication Scale of the Fondazione Don Gnocchi (FDG-CCS).MethodsSix Intensive Neurorehabilitation Units enrolled consecutively admitted patients with severe brain injury. Demographic, anamnestic, and clinical data were collected at study entry. For each enrolled patient, two independent examiners (A and B) administered the FDG-CCS considering 2 weeks as an observation time window. Concurrently, a third examiner (C) administered the Comorbidities Coma Scale. The blinded examinations were analyzed to assess the inter-rater agreement (A vs. B) and the concurrent validity of the FDG-CCS with respect to the Comorbidities Coma Scale (C).ResultsA total of 42 patients (22 patients with and 20 emerged from prolonged disorder of consciousness) were enrolled. The FDG-CCS total score did not differ in the two subgroups of patients. Metabolic (examiner A = 33%; examiner B = 43%), gastro-intestinal (A = 31%; B = 26%), cardio-vascular (A = 26%; B = 29%), respiratory (A = 21%; B = 21%), and musculo-skeletal disorders (A = 19%; B = 14%) were the most frequent complications. Inter-rater agreement for the total score of the FDG-CCS resulted to be good (intra-class correlation coefficient = 0.865; p < 0.05), and the FDG-CCS total score correlated significantly with the total score of the Comorbidities Coma Scale (A, ρ = 0.356; p = 0.01; B, ρ = 0.317; p = 0.02).DiscussionThe present multicenter study proposed and validated a novel clinical tool for the categorization of clinical complications of patients with severe brain injury. This clinical tool could help the rehabilitation team for planning tailored treatment and prevention of clinical complications that negatively impact patients’ outcomes and hamper rehabilitation programs.